Implementation of Break Event Point Analysis and Margin of Safety in Profit Planning - Naning Fatmawatie (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2021)
The break event point is a certain amount of production that the company must achieve to reach the break-even point (no profit and / no loss). Margin of safety is the amount of production required so that the company does not suffer losses. The determination of the margin of safety is closely related to the break event point, where the margin of safety is at one level above the break event point in terms of determining the minimum sales required. Both of these are some of the instruments that can be used to plan profits. The purpose of this study was to determine the application of break event point analysis at PT. Beton Jaya Manunggal, knowing the application of margin of safety analysis and to determine profit planning at PT. Jaya Manunggal Concrete. This study uses a non-statistical quantitative approach. The data used in this study is secondary data through PT. Manunggal Jaya Concrete in 2014-2018. The analysis method uses the least square method to plan the net profit of PT. Beton Jaya Manunggal in 2019 with reference to the net sales plan. The result of this research is the break event point of PT. Beton Jaya Manunggal in 2014 – 2018 showed a positive trend with the break event point being above the current year's production during 2015 – 2016. Margin of safety PT. Beton Jaya Manunggal in 2014 – 2018 showed an upward trend with negative margins throughout 2015 – 2016. Profit planning using least squares with reference to net sales planning is quite accurate considering that there is only a difference of 2% above net sales recorded in the 2019 financial statements. Net profit PT. Beton Jaya Manunggal was recorded in 2019 at 1.3 billion Rupiah so that profit planning was not carried out based on the consideration that the recorded profit was less or showed a downward trend when compared to the net profit trend in 2014 – 2018.